2013
DOI: 10.1017/s0003598x00048729
|View full text |Cite
|
Sign up to set email alerts
|

Burial mounds and settlement patterns: a quantitative approach to their identification from the air and interpretation

Abstract: The author describes a process of systematic integration of aerial and satellite imagery, which has provided a huge increase in the number of known burial mounds in the area where the Danube meets the Black Sea. Careful evaluation of newly acquired and archival imagery from satellites and lower level platforms shows where data is comparable and how visibility varies with imagery type. Excavations to date suggest the majority of the mounds are of Greco-Roman date and associated with the large towns and their ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Bromus sterilis, Carduus acanthoides and Onopordum acanthium), terrestrial reed (Phragmites communis), native woody species (Crataegus monogyna and Sambucus nigra) and invasive woody species (especially Robinia pseudoacacia and Elaeagnus angustifolia) were reported as major biotic threatening factors (Tóth and Tóth 2003;Moysiyenko and Sudnik-Wójcikowska 2008;Barczi et al 2009). We found that most of the threatening factors, even the biotic ones, were associated with some kind of human activity, and mostly linked with the intensification of land use (Rowińska et al 2010;Kuksova 2011;Sudnik-Wójcikowska et al 2011, 2013Rákóczi and Barczi 2014). Accordingly, there was a decreasing trend from the west to the east in the presence and intensity of ploughing, establishment of orchards, use of chemicals, soil extraction, building of settlements and roads.…”
Section: Construction Work and Urbanisationmentioning
confidence: 96%
See 3 more Smart Citations
“…Bromus sterilis, Carduus acanthoides and Onopordum acanthium), terrestrial reed (Phragmites communis), native woody species (Crataegus monogyna and Sambucus nigra) and invasive woody species (especially Robinia pseudoacacia and Elaeagnus angustifolia) were reported as major biotic threatening factors (Tóth and Tóth 2003;Moysiyenko and Sudnik-Wójcikowska 2008;Barczi et al 2009). We found that most of the threatening factors, even the biotic ones, were associated with some kind of human activity, and mostly linked with the intensification of land use (Rowińska et al 2010;Kuksova 2011;Sudnik-Wójcikowska et al 2011, 2013Rákóczi and Barczi 2014). Accordingly, there was a decreasing trend from the west to the east in the presence and intensity of ploughing, establishment of orchards, use of chemicals, soil extraction, building of settlements and roads.…”
Section: Construction Work and Urbanisationmentioning
confidence: 96%
“…The proportion of kurgans covered by arable lands decreases from west to east and from lowland to upland regions. Horticulture on kurgans is mentioned from Hungary and Bulgaria (Tóth 1998;Oltean 2013). The presence of settlements on kurgans is typical in the western regions (Hungary and Romania; Bede 2012; Oltean 2013).…”
Section: Land Cover Types and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimating their total number seems impossible and those not registered as archaeological sites are continually facing destruction. (1) Systematic mapping studies using old cartographic documents and field surveys are exceptions and only cover small regions, such as northern Muntenia (Frînculeasa et al, 2017a) and Dobruja (Topoleanu et al, 2008;Oltean, 2013). Still, the number of existing mounds is probably closer to several thousand.…”
Section: Mots-clésmentioning
confidence: 99%